2007
DOI: 10.1017/s0016672307008610
|View full text |Cite
|
Sign up to set email alerts
|

Gametogenesis of intergroup hybrids of hemiclonal frogs

Abstract: European water frog hybrids Rana esculenta (R. ridibundarR. lessonae) reproduce hemiclonally, by hybridogenesis : in the germ line they exclude the genome of one parental species and produce haploid gametes with an unrecombined genome of the other parental species. In the widespread L-E population system, both sexes of hybrids (E) coexist with R. lessonae (L). They exclude the lessonae genome and produce ridibunda gametes. In the R-E system, hybrid males coexist with R. ridibunda (R); they exclude either their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 17 publications
(18 reference statements)
2
34
0
1
Order By: Relevance
“…; Tunner and Heppich‐Tunner ; Ragghianti et al. ). We also found few, probably, recombinant diploid hybrids in the Seversky Donets River drainage.…”
Section: Discussionmentioning
confidence: 99%
“…; Tunner and Heppich‐Tunner ; Ragghianti et al. ). We also found few, probably, recombinant diploid hybrids in the Seversky Donets River drainage.…”
Section: Discussionmentioning
confidence: 99%
“…This can be verified by means of experimental crosses. A first attempt of such crosses between water frogs of the L-E and R-E system has been made by Ragghianti et al (2007). They concluded that a particular combination of the R-E system lessonae genome and the R-E system ridibundus genome is necessary to induce a ridibundus genome elimination (Ragghianti et al 2007).…”
Section: The Impact Of Translocations In the Water Frog Complexmentioning
confidence: 99%
“…Furthermore, previous studies have shown that PR is a ubiquitous amphibian, breeding in a wide variety of flowing and stagnant waters such as rivers, brooks, dead arms, reservoirs and lakes (Pagano et al 2001;Van Buskirk 2003), as well as smaller bodies of water, such as ponds in gravel beds (Joly and Morand 1994;Morand and Joly 1995). As a consequence, this invasion has had an impact on closely related Ranid taxa, observed in the form of competition at the larval stage (Luquet et al 2011) and also in genetic introgression (Holsbeek and Jooris 2010;Hotz and Uzzell 1983;Hotz et al 1985;Plötner et al 2008;Ragghianti et al 2007). However, the consequences of this colonization on other amphibian native species have not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%